2013
DOI: 10.1002/dmrr.2362
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycated albumin isolated from poorly controlled type 1 diabetes mellitus patients alters macrophage gene expression impairing ABCA‐1‐mediated reverse cholesterol transport

Abstract: (Carboxymethyl)lysine-modified albumin isolated from poorly controlled type 1 diabetic patients impairs ABCA-1-mediated reverse cholesterol transport and elicits intracellular lipid accumulation, possibly contributing to atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
3
37
0
7
Order By: Relevance
“…Our group (Passarelli et al, ; Castilho et al, ; Machado‐Lima et al, ) and others (Isoda et al, ) have shown that AGE reduce ABCA‐1 protein content independent of changes in its mRNA expression. In fact, this reduction was observed in the present study in incubations with DM2‐HSA, which affected protein content without changes in mRNA levels.…”
Section: Discussionmentioning
confidence: 67%
“…Our group (Passarelli et al, ; Castilho et al, ; Machado‐Lima et al, ) and others (Isoda et al, ) have shown that AGE reduce ABCA‐1 protein content independent of changes in its mRNA expression. In fact, this reduction was observed in the present study in incubations with DM2‐HSA, which affected protein content without changes in mRNA levels.…”
Section: Discussionmentioning
confidence: 67%
“…Advanced glycation is independently related to cardiovascular disease, by inducing oxidative and inflammatory stress and disturbing the flux of cholesterol from the artery wall to the liver in the reverse cholesterol transport pathway. This may contribute to atherogenesis in diabetes mellitus (DM), chronic kidney disease, and inflammatory diseases [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular cholesterol efflux was also measured in a subgroup of volunteers (6 hypo, 6 controls and 7 hyper); J774 macrophages enriched with acetylated LDL and 14 C-cholesterol, using HDL as the cholesterol acceptor, as described earlier (Machado- Lima et al, 2013). Briefly, J774 macrophages were cultured in RPMI 1640 medium containing 10% fetal calf serum, penicillin and streptomycin and maintained in a 5% CO 2 incubator at 37°C.…”
Section: Cellular Cholesterol Effluxmentioning
confidence: 99%